La gestión administrativa financiera y su incidencia en la reserva ecológica mache chindul, cantón Quinindé, provincia de Esmeraldas, periodo 2013 - Montenegro Muñoz, Miryan Elizabeth (2014)
In the present investigation whose Topic is "The Gestion Administrative Financial Management of the Ecological Reservation Mache Chindul, it has been considered, starting from the great quantity of people that works in the different companies linked in the tourist sector, they should have the enough and permanent back of the public, private and community entities in order to transform them into a prop of the development of the country. Also, also to the trade, transport, crafts, etc., To which have not been given the respective importance, in spite of being inmersos in the tourism. The objective of this investigation The Gestion Administrative Financial Management of the Ecological Reservation Mache Chindul of the Canton Quinindé. It is important to know the advances and achievements in the actions, processes and ecological activities that will allow completing the objectives of the area, as well as which the problems or critical aspects are that it is necessary to face and in what elements the protected area is strengthened. Knowing the situation in which are the actions and components of the handling, will be easier for the administration of the area, to make decisions, with clear knowledge of the problems and their causes. Inside this context the evaluation of the handling efficiency constitutes an important tool to improve the administration strategies, to make more efficient the actions and programs of financial handling. The methodology is adapted for the analysis and interpretation of the data that intend with a highly up-to-date proposal.